Exploring Research Trends in Air-rail Passenger Transport Relationships Through a Content-based Analysis - Waralee Peetawan Rattanakijsuntorn; Nitjanan Sualoy; Kittiwadee Pienpookhao (My University, 2022)
Background: Air and rail passenger transport was initially considered to be competitive. However, as both modes have been developed, several other forms of relationships have been introduced and become more complicated, leading to the investigation of research trends in the air-rail passenger transport relationship. Gap: There are few studies on the relationships between air and rail passenger transport, lacking research synthesis application. Aims: This paper classifies and analyzes the relationships between air and rail passenger transport based on research publications between January 2006 and December 2020. Objectives: The objective of this study is 1) to investigate the possible forms of relationships the air-rail passenger transport based on existing studies, 2) to reveal research themes and trends, and 3) to propose research potentials in the air-rail passenger transport. Methods: The study uses a content-based analysis by deriving research articles from transportation and databases. A total of 472 articles were initially identified and screened. One hundred and forty-five articles were included in the final synthesis. Results: Air-rail relationships were categorized as a modal comparison, competition, cooperation, integration and influence. Research has been found to rely heavily on the mixture of modal competition, integration and influence. Furthermore, it has been pointed out that the influence between air and rail passenger transport has a one-way effect; air carriers are affected by the entrance of high-speed trains but not in a reverse direction. China has been an emerging context of this topic over the past five years and is likely to dominate the air-rail research due to its extensive high-speed rail networks and vast developments in large airports. Conclusion: In terms of the air-rail infrastructure development, it was suggested that modal cooperation was outdated due to lacking seamless connectivity features. Future research might explore the deficient research disciplines, including transport sustainability, business practices and tourism, as well as the impact of the coronavirus disease pandemic in reshaping the air-rail passenger transport industry.
Keywords: Passenger transport; Aviation Industry Analysis and Trends